2005
DOI: 10.1105/tpc.104.027441
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of NIMIN1 with NPR1 Modulates PR Gene Expression in Arabidopsis

Abstract: The Arabidopsis thaliana NONEXPRESSER OF PR GENES1 (NPR1, also known as NIM1) protein is an essential positive regulator of salicylic acid (SA)-induced PATHOGENESIS-RELATED (PR) gene expression and systemic acquired resistance (SAR). PR gene activity is regulated at the level of redox-dependent nuclear transport of NPR1. NPR1 interacts with members of the TGA family of transcription factors that are known to bind to SA-responsive elements in the PR-1 promoter.In an attempt to identify proteins involved in SA-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
1
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(178 citation statements)
references
References 63 publications
(67 reference statements)
10
155
1
4
Order By: Relevance
“…In plants, EAR motifs are found on a number of transcriptional regulators and they are sufficient to repress transcription (Ohta et al, 2001). It is not clear (Weigel et al, 2005;Kazan, 2006). Our work shows that the XopD EAR motifs are required to repress plant gene transcription, to promote maximal Xcv multiplication, and to delay the onset of disease symptoms infected tomato leaves (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In plants, EAR motifs are found on a number of transcriptional regulators and they are sufficient to repress transcription (Ohta et al, 2001). It is not clear (Weigel et al, 2005;Kazan, 2006). Our work shows that the XopD EAR motifs are required to repress plant gene transcription, to promote maximal Xcv multiplication, and to delay the onset of disease symptoms infected tomato leaves (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 83%
“…We currently favor the model that XopD may be functioning at the level of chromatin-remodeling based on the finding that ERF7, an Arabidopsis EAR-containing protein, appears to be altering chromatin status by recruiting the corepressor SIN3 and histone deacetylase HDA19 to promoters containing GCC boxes (Song et al, 2005;Weigel et al, 2005;Kazan, 2006). Also, the overexpression of ORE7, nuclear chromatin remodeling, AThook DNA binding motif prolongs leaf longevity in Arabidopsis (Lim et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…However, fusion of the bait protein with a heterologous DNA binding domain or fusion of the prey protein with an activation domain might hamper certain interactions. In the screen reported here, this potential drawback was circumvented by positioning three copies of the as-1 element (3x as-1) upstream of the HIS3 selectable marker gene (Weigel et al, 2005) and expressing TGA2 in trans. As as-1-bound TGA2 only weakly activates transcription in yeast, the resulting strain does not grow on selective medium when 15 mM 3-amino-1,2,4-triazole is added.…”
Section: Identification Of Tga-interacting Protein Scl14 By a Yeast Pmentioning
confidence: 99%
“…De hecho, su sobreexpresión compromete respuestas defensivas como la ETI y la SAR. Además, también puede formar complejos con algunas TGAs, NPR1 y el promotor PR-1, modulando así la activación transcripcional dependiente de los TGAs (Weigel et al 2001;Weigel et al 2005).…”
Section: Percepción Del Sa: Dependiente E Independiente De Npr1unclassified
“…There are two families of NPR1 interactors: TGAs (Zhang et al 1999) and NIMINs (Weigel et al 2001). Only when knocking out several genes (TGAs, Zhang et al 2003), or expressing dominant members (NIMINs, Weigel et al 2005), is a measurable phenotype observed in SA signalling.…”
Section: Introductionmentioning
confidence: 99%